Oral Scutellarin Treatment Ameliorates Retinal Thinning and Visual Deficits in Experimental Glaucoma - Zhu, Jingyuan; Sainulabdeen, Anoop; Akers, Krystal; Adi, Vishnu; Sims, Jeffrey R.; Yarsky, Eva; Yan, Yi; Yu, Yu; Ishikawa, Hiroshi; Leung, Christopher K.; Wollstein, Gadi; Schuman, Joel S.; et al. (Frontiers in Medicine, 2021)
Purpose: Intraocular pressure (IOP) is currently the only modifiable risk factor for glaucoma, yet glaucoma can continue to progress despite controlled IOP. Thus, development of glaucoma neurotherapeutics remains an unmet need. Scutellarin is a flavonoid that can exert neuroprotective effects in the eye and brain. Here, we investigated the neurobehavioral effects of scutellarin treatment in a chronic IOP elevation model. Methods: Ten adult C57BL/6J mice were unilaterally injected with an optically clear hydrogel into the anterior chamber to obstruct aqueous outflow and induce chronic IOP elevation. Eight other mice received unilateral intracameral injection of phosphate-buffered saline only. Another eight mice with hydrogel-induced unilateral chronic IOP elevation also received daily oral gavage of 300 mg/kg scutellarin. Tonometry, optical coherence tomography, and optokinetics were performed longitudinally for 4 weeks to monitor the IOP, retinal nerve fiber layer thickness, total retinal thickness, visual acuity, and contrast sensitivity of both eyes in all three groups. Results: Intracameral hydrogel injection resulted in unilateral chronic IOP elevation with no significant inter-eye IOP difference between scutellarin treatment and untreated groups. Upon scutellarin treatment, the hydrogel-injected eyes showed less retinal thinning and reduced visual behavioral deficits when compared to the untreated, hydrogel-injected eyes. No significant difference in retinal thickness or optokinetic measures was found in the contralateral, non-treated eyes over time or between all groups. Conclusion: Using the non-invasive measuring platform, oral scutellarin treatment appeared to preserve retinal structure and visual function upon chronic IOP elevation in mice. Scutellarin may be a novel neurotherapeutic agent for glaucoma treatment.